Sang Lain Dalam Novel Kekasih Musim Gugur Karya Laksmi Pamuntjak: Sebuah Kajian Feminisme Eksistensialis Simone De Beauvoir - Puteri, Estri Ristra; Maharani U, Nazla; Harjito (Jurnal Nusantara Raya, 2024)
Abstract: This study aims to describe the existence of women as the Other in the novel and the interrelationships between elements that can provide a strong relationship between the characters and the setting using the issue of self-awareness in the perspective of feminism (Simone de Beauvoir's existentialist feminism). The data in this study are in the form of descriptions and dialogues related to female characters. This study uses two sources of data, namely the novel Kekasih Autumn by Laksmi Pamuntjak and also books or literature journals that are relevant to the research. The data collection technique in this research is documentation or documentary studies, namely how to collect data through documented or documentary materials. This study uses structural analysis. The results of the study found that the existence of women can be investigated through the female character and setting in the novel Kekasih Autumn Autumn, while the efforts of women to achieve their existence in the novel Kekasih Autumn consist of 4 strategies according to Simone de Beauvoir, namely (1) Women can work, (2) Women can become intellectuals, (3) Women can work to achieve socialist transformation of society, (4) Women can reject the Other – that is, by identifying themselves through the views of the dominant group in society.